The teaching of Modern Standard Arabic collocations from a translation approach - Amehdar, Abdelmajid (Anaquel de Estudios Árabes, 2024)
This article discusses in detail the issues related to the teaching of Modern Standard Arabic collocations in multilingual contexts, taking as a case the French schools in Morocco. In this context, the main taxonomies that have been developed in recent years will also be studied to find out what type of collocation should be introduced in the classroom, with all the advantages that this entails. Then, we will see how to select and present them before memorizing and reusing them. Next, some collocational errors will be analyzed, taking into account the intrinsic characteristics of these lexical units and the difficulties involved in their learning. Hence, we will need to examine this issue from a translation approach, based on the theories of the teaching of second languages. This procedure will allow us to learn them in a practical and contextualized way according to their communicative function. In particular, this objective will be achieved through activities likely to adequately develop the phraseological competence of the users.
Keywords: Modern Standard Arabic; Collocations; Taxonomies; Errors; Activities; Target language